2018
DOI: 10.1111/epi.14508
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of hospital admission for ICD‐9‐CM psychotic episodes following admission for epilepsy

Abstract: An epilepsy admission was independently associated with subsequent hospital readmission for psychotic episodes, even after adjustment for confounding variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In addition, a psychopathology study revealed that greater severity of ASD symptoms and male sex were related to the higher risk of progression to schizophrenia 2 . Systemic autoimmune diseases, neurological diseases, and other physical illnesses have been suggested as risk factors for psychotic symptoms and schizophrenia 14,15 . A population‐based study indicated a positive association between systemic lupus erythematosus and schizophrenia among patients of different ages, gender, and socioeconomic status 16 …”
mentioning
confidence: 99%
“…In addition, a psychopathology study revealed that greater severity of ASD symptoms and male sex were related to the higher risk of progression to schizophrenia 2 . Systemic autoimmune diseases, neurological diseases, and other physical illnesses have been suggested as risk factors for psychotic symptoms and schizophrenia 14,15 . A population‐based study indicated a positive association between systemic lupus erythematosus and schizophrenia among patients of different ages, gender, and socioeconomic status 16 …”
mentioning
confidence: 99%
“…Medical comorbidities such as hypertension, diabetes, renal disease, coagulopathies, autoimmune disease, sepsis, and psychiatric disorders were identified using validated ICD‐9‐CM codes 13 from previously published studies and/or Clinical Classification Software codes, which consist of grouped ICD‐9‐CM codes developed as a publicly available software tool via HCUP 24–29 . Codes for nausea and vomiting and rheumatoid arthritis were obtained from manual review of ICD‐9 codes.…”
Section: Methodsmentioning
confidence: 99%
“…grouped ICD-9-CM codes developed as a publicly available software tool via HCUP. [24][25][26][27][28][29] Codes for nausea and vomiting and rheumatoid arthritis were obtained from manual review of ICD-9 codes. Additional covariates such as age and income quartile were obtained from the NRD.…”
Section: Key Pointsmentioning
confidence: 99%
“…Participants were purposively selected, and the prospective participants' files were sorted with the assistance of record officers before being reviewed by the investigator and nurses on duty. Inclusion criteria were that the individual had to have a diagnosis of schizophrenia and been mentally stable for not less than 3 months (research evidence shows that the risk of relapse is usually high from 1-3 months of discharge 28 ). Exclusion criteria were records of positive symptoms in the last 3 months (which can impede the interview process, such as flight of idea or slurred and incoherent speech), history of debilitating co-morbidity (such as head injury, cerebral cancer, poorly managed diabetes with injuries or wounds), affective co-morbidities (such as depression and mania) and individuals younger than 18 years.…”
Section: Sampling and Procedures For Data Collectionmentioning
confidence: 99%